MOKESTINĖS PRIEVOLĖS TEISINĖ PRIGIMTIS: UKRAINOS IR LIETUVOS RESPUBLIKOS ĮSTATYMŲ LYGINAMOJI ANALIZĖ - Oliynyk, A. (Teisė, 2014)
The article discussed the content of the obligation to pay taxes as one of the main duties of the taxpayer. Legal nature of the constitutional duty for taxes and fees payment has been investigated on the basis of analysis of the Fundamental Law of Ukraine and Republic of Lithuania. Subject to the provisions of the Tax Code of Ukraine and special law Republic of Lithuania examines the nature of the obligation to pay taxes. The attention is focused on the content of the category of “fiscal responsibility”, in particular on the problem of its relations with the term “tax liability”.